Modeling and sliding mode control for a single flexible manipulator - Hoang, Nguyen Quang; Son, Ha Anh (Vietnam Journal of Science and Technology, 2019)
This paper concerns with modeling and control of a single flexible manipulator (SFM). The finite element method (FEM) and Lagrangian equations are exploited to establish the dynamic modeling of SFM. Firstly, the Jacobian matrix is built based on kinematic analysis. Then it is used in construction of a mass matrix for each element. The position and vibration of SFM are controlled by sliding mode controller (SMC). Its parameters are chosen by linearized equations to guarantee the stability of the system. The numerical simulation is carried out to show the efficiency of the proposed approach.